Who should have carotid surgery or angioplasty? - Rothwell, P (2000)
Carotid endarterectomy reduces the overall risk of stroke in patients with ECST70-99% recently symptomatic stenosis, and to a lesser extent, at least in the short-term, in patients with severe asymptomatic stenosis. Whether angioplasty and stenting is a reasonable alternative will be decided by the results of ongoing RCTs of angioplasty versus endarterectomy. The current policy of operating on all patients with a recently symptomatic severe carotid stenosis will, on average, do more good than harm. However, the number of patients needed to treat to prevent one stroke is still relatively high. The effectiveness of endarterectomy could be improved by selecting patients more rigorously. Subgroup analysis and risk factor modelling are likely to be of some value, but further testing is required before final models can be recommended for routine use in clinical practice. However, it is also likely that predictive models will eventually also take into account information on cerebral microemboli, cerebral perfusion, and genetic characteristics. The development and validation of integrated predictive models, combining these different modalities, will require large prospective clinical studies.